Cost Effective Ossicular Reconstruction- A Case Report: Life Sciences-Medicine - Ramanathan, Sumitha; Govarthanaraj, Aberna (International Journal of Life Science and Pharma Research, 2022)
Ossicular reconstruction using various materials from autograft to artificial prosthesis have a wide range of success and failure rates due to various reasons. In this article, a newer use of old grommet in ossicular reconstruction is attempted. A 50yr old lady presented with hearing loss in the right ear for one year. She gave a previous history of ear discharge 11 months back. There was no other positive history relevant to the case. On examination, the pars tensa was plastered and immobile on the left side. Her Pure tone audiometry showed conductive hearing loss on the left ear with average 55 db loss. Her CT showed absent incus with obliteration of middle ear-space and sclerosed mastoid. We planned for Tympanotomy. On elevating the flap, the incus and stapes were absent. Here we decided on a newer use for the grommet and used it as prosthesis. The result is good and promising with no complications. The grommet did not get extruded or produce granulation tissue. The ear is dry and the patient is still on follow up. The purpose of publishing this report is to identify a prosthesis that is cost-effective and readily available. The grommet has been used for a more extended period for other indications,but as a prosthesis for reconstruction is a new method and requires further studies.